Dose Evaluation of Head and Neck Cancer IMRT Treatment Planning Based on Gamma Index Analysis of Varian Halcyon 2.0 Linac - W. Purwati; F. Suhaimi; W. E. Wibowo; S. A. Pawiro (National Research and Innovation Agency, 2023)
Varian Halcyon 2.0 linear accelerator was launched and became available for clinical use in 2018. Therefore, it is necessary to evaluate the accuracy of exit fluence of the Halcyon 2.0 for quality assurance (QA) of head and neck cancer treatment planning, pretreatment, and treatment. The accuracy of the exit fluence for twenty treatment plannings has been evaluated by conducting gamma analysis for QA pretreatment and treatment in each field and composite field by using criteria for gamma index 3 %/3 mm and 2 %/2 mm. The QA pretreatment results are in the average value for each criterion for each field and composite fields on actual gantry angle and null gantry angle with gamma passing rate (GPR) of over 99 % (range 99.78 %-99.95 %) The total treatments consisted of 2717 fractions. The analysis results of GPR for fields were 99.32 % and 97.74 % for gamma indexes of 3 %/3 mm and 2 %/2 mm, respectively. In addition, the analysis results of GPR for composites were 95.46 % and 81.38 % for gamma indexes of 3 %/3 mm and 2 %/2 mm, respectively. Based on this result, the average GPRs of QA pretreatment are ≈ 99 % of the total pixels. This means the prediction dose of Varian Halcyon 2.0 is accurate. The average GPRs of treatment is nearly 90 %, showing that Varian Halcyon 2.0 is effective for creating treatment plans for complex cases.